(untitled) (American Journal of Applied Statistics and Economics, 2024)
Since modern times, with the rapid development of the economy and the improvement of people’s living standards, people have gradually begun to pay attention to green environmental protection, attach importance to the development of green economy, and at the same time, the development of green economy has also put forward the adjustment and optimization of industrial structure. Today’s green economy has become the trend of the times, and it is an economic development path to realize the harmony between man and nature. Continuously strive to promote the green and low-carbon transformation of energy, it will provide important support and reference for the development of renewable energy in the Republic. Based on the analysis of the literature and the data of the National Bureau of Statistics, this paper puts forward the problems existing in today’s green ecological economy, and gives relevant reasonable suggestions for these problems, hoping to provide relevant references for energy economy enterprises, so as to promote complementary advantages and promote the development of national energy transformation. In order to promote the economic value and economic development significance of green economy in ecological and environmental protection, so as to realize the prospect of green economic development from the perspective of ecological and environmental protection, and the effective path of today is discussed and summarized, in order to help the development of China’s green economy.